Peran Pemikiran Ibnu Taimiyah dalam Mengikis Sinkretisme (Studi Analisis Deskriptif Menuju Peradaban Islam Puritan) - Salem Sunardi Basri; Sarbini Sarbini Anim; Hidayatullah Hidayatullah Hidayatullah; Sunardi Bashri Iman (Fakultas Dakwah dan Ilmu Komunikasi, 2026)
Syncretism is a cause of the decline and weakening of civilization, such as mysticism, superstition, and heresy. This qualitative research uses a descriptive analysis design to identify concrete steps taken by Ibn Taymiyyah in eradicating syncretism. The new research findings indicate that Ibn Taymiyyah took the following steps to eradicate syncretism: first, strengthening monotheism and the absence of polytheism; second, improving worship; third, fostering noble morals; and fourth, avoiding religious fanaticism.